Short Communication: Assessing phytoplankton species structure in trophically different water bodies of South Ural, Russia - Anastasiya M. Kostryukova; IRINA MASHKOVA; SERGEY BELOV; ELENA SHCHELKANOVA; VIKTOR TROFIMENKO (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Kostryukova A, Mashkova I, Belov S, Shchelkanova E, Trofimenko V. 2021. Short Communication: Assessing phytoplankton species structure in trophically different water bodies of South Ural, Russia. Biodiversitas 22: 3530-3538. The study aims to analyze the species structure of the phytoplankton communities of four water bodies in South Ural (Lakes-Turgoyak, Uvildy, Ilmenskoe and Shershnevskoe reservoir). These water bodies are characterized by different trophic states and levels of anthropogenic impact. Lake Turgoyak is oligotrophic; Lake Uvildy is oligomesotrophic. Both water bodies are protected areas and natural monuments. But tourism and recreation are not prohibited on their territories. The mesoeutrophic Lake Ilmenskoe is partially located within the Ilmen State Reserve, and it experiences less anthropogenic impact. The eutrophic Shershnevskoe reservoir is located within the boundaries of the city of Chelyabinsk. It is used as a source of drinking water. Cyanobacteria was the dominant division in the eutrophic Shershnevskoe reservoir. Bacillariophyta dominated in the plankton communities in oligotrophic Lake Turgoyak and oligomesotrophic Lake Uvildy. Green and blue-green algae biodiversity increased in the oligomesotrophic Lake Uvildy. For the mesoeutrophic Lake Ilmenskoe, diatom algae are dominant, but a higher proportion of Chlorophyta (especially Cyanobacteria) was revealed. Species similarity among phytoplankton communities in the given lakes was studied through cluster analysis based on the Sorensen-Czekanowski coefficient. The higher level of similarity between plankton species compositions could be explained by their locality rather than their trophic status.